ENGLISH AND UZBEK ARTISTIC STYLE AND TRANSLATION PROBLEMS (Proceedings of International Conference on Educational Discoveries and Humanities, 2024)
Fiction is an important field that reflects the culture, history and spirit of each nation. Each language has its own artistic style, which determines the content, structure and methods of expression of literary works. The differences between English and Uzbek artistic styles cause many problems in the translation process. In this article, we will discuss in detail the specific aspects of English and Uzbek artistic styles, their cultural context, and problems in the translation process.